Pondering the Legacy of Geo Widengren: Isolated Genius, or Uncritical Supporter of a Band of Brothers? - Larsson, Göran (Method & theory in the study of religion, 2023)
This article is both an introduction to a collection of papers that critically discuss and evaluate the volume The Legacy, Life and Work of Geo Widengren and the Study of the History of Religions after World War II, which I edited and published with Brill in 2021, as well as an opportunity for me to think with and about the Swedish historian of religions, Geo Widengren (1907–1996). Widengren was the holder of the chair in the History of Religions and Psychology of Religions at Uppsala University between 1940 and 1973.